Status Gizi dan Prestasi Belajar Remaja SMA : Peran Stres Akademik sebagai Efek Modifikasi - Syafani, Muhammad Rizqi (Jurnal Skala Kesehatan, 2026)
Nutritional status and academic stress are suspected to influence adolescent academic achievement; therefore, this study aimed to analyze the relationship between nutritional status and academic achievement and the role of academic stress as a modifying factor among 10th-grade students of SMAN 14 Bandung. This analytical observational study with a cross-sectional design involved 123 adolescents selected by consecutive sampling from Januari to April 2025. Nutritional status was determined using body mass index-for-age according to the 2020 Indonesian Ministry of Health guidelines, academic achievement was measured by report card average scores, and academic stress was assessed using the Educational Stress Scale for Adolescents. Overall, no significant relationship was found between nutritional status and academic achievement (p = 0.859); however, after stratification by stress level, a significant difference appeared in the normal-to-mild stress group (p = 0.038) but not in the very severe stress group (p = 0.427). High academic stress can mask the benefits of good nutritional status on academic performance. Most adolescents were overweight (51.2%). Improving adolescent academic achievement requires a dual approach of balanced nutrition improvement and effective academic stress management through education, counselling, and supportive school and family environments.